The Application of the Team Game Tournament (TGT) Model in Enhancing Motivation and Learning Outcomes in Islamic Religious Education (PAI) at SMA Negeri 1 Tambakboyo - Much Machfud Arif; Faridatul Latifah; Miftahul Shofiyatul Ulya; Lailatul Khasanah (LP3M KH Yazid Karimullah Institute, 2025)
Abstract. The purpose of this research is to apply the teams games tournament (TGT) model in learning activities which is expected to be able to increase the motivation and learning outcomes of students in grades X-5 which are relatively low. The research method used is classroom action research (PTK). Using two cycles through four steps, namely planning, implementation, observation, and reflection. This research in data collection uses observation, documentation, and test techniques. The results of this study show that before the action was taken, only 12 students achieved a score above 70 with an average of 60.2 and a completion percentage of 31.55% which shows a very poor category. However, after the implementation of the action in the first cycle, there were 19 students who achieved a score above 70 with an average of 68.8 and a completion percentage of 50% which increased by 19.5% compared to before. Furthermore, in the second cycle there were 33 students who achieved a score above 70 with an average of 83 and a completion percentage of 86.8%, which increased by 36% compared to the first cycle. In addition, students also become more motivated to be active during learning activities so that it also affects learning outcomes. Thus, the application of the TGT model has proven to be successful in increasing the motivation and learning outcomes of PAI class X-5 at SMA Negeri 1 Tambakboyo.